PENJADWALAN PREVENTIF MAINTENANCE MESIN AIR HANDLING UNIT (AHU) DI PT.X MENGGUNAKAN METODE RCM - Febiansyah, Aditya; Febryanto, Indra Dwi (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2025)
Air Handling Unit (AHU) plays an important role in maintaining air quality in pharmaceutical production areas. At PT. X, recurring AHU failures cause significant downtime and disrupt productivity. This study aims to optimize preventive maintenance scheduling by applying the Reliability-Centered Maintenance (RCM) method. Analysis of critical components is carried out using Failure Mode and Effect Analysis (FMEA) to determine the Risk Priority Number (RPN), and time-to-failure (TTF) data is processed using Minitab 21 software. Identified critical components include condenser, blower, compressor, and evaporator. The results show that the lognormal distribution is the most suitable for most components, except for the compressor which follows a Weibull distribution. The optimal preventive maintenance interval is calculated based on MTBF values. Implementing this schedule is expected to reduce downtime and improve AHU reliability. Keyword : keyword1, keyword2, keyword3, keyword4 (follow alphabetical).